Early Childhood Character Development Through Fairytale Media (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The purpose of this study was to determine whether or not the influence of fairy tales as a medium for character development in early childhood. Fairy tale itself is a story that did not really happen or an imaginary story, and character cultivation is the provision of an education that forms morals or character that distinguishes one person from another. The sample taken was the TBM group (Taman Belajar Membaca) which consisted of 20 children aged 5-6 years. The method used is a type of qualitative research, with data collection from observations and interviews. The results of the research obtained are fairy tales as a medium in character development are very effective to be applied to early childhood and the need for habituation and good examples to grow the character of children.